Developing Personally Relevant Goals for People with Mild Dementia - Khayum, Becky; Wynn, Rachel (Seminars in Speech and Language, 2015)
Many speech-language pathologists work in the skilled nursing facility setting and frequently treat patients in subacute rehabilitation who are experiencing mild cognitive deficits as a result of dementia. Treatment of these individuals needs to be carefully differentiated from rehabilitative treatment of a stroke or traumatic brain injury. A “habilitation” approach should be considered, focusing on an individual's preserved strengths and developing patient-centered goals that focus upon the integration of personally relevant stimuli into the care plan. Environmental modification, the use of visual memory aids, counseling, and ongoing family education are also essential components of this approach. This case study is a thorough example of how the habilitation approach can be used to provide intervention for a person with mild dementia. The case study will explain indication for treatment, assessment, goal selection, and research to support the treatment plan.
Keywords: Evidence-based practice (EBP); dementia; habilitation; caregiver education; skilled nursing; long-term care